Transanal hemorrhoidal dearterialization (THD) for hemorrhoidal disease: An Italian single-institution 5-year experience analysis and updated literature review - Verre, Luigi; Gallo, Gaetano; Grassi, Giulia; Bussolin, Edoardo; Carbone, Ludovico; Poto, Gianmario Edoardo; Carpineto Samorani, Osvaldo; Marano, Luigi; Marrelli, Daniele; Roviello, Franco (Frontiers in Surgery, 2022)
Background: Hemorrhoidal disease is a highly prevalent, chronic disorder that usually compromise patients’ quality of life. Despite recent advances in pharmacologic and surgical therapeutic options, a clear treatment "gold standard" is lacking. Our aim is to analyze the outcomes following Transanal Hemorrhoidal Dearterialization (THD) procedure. Methods: Patients who failed conservative treatment and underwent THD Doppler between 2017 and 2021 were enrolled. Follow-up interviews (consisting of clinical examination, Visual Analog Scale for pain - VAS, Vaizey incontinence score, Hemorrhoid Severity Score) were administered 1 week, 2 weeks, 1 month and 6 months after surgery. Results: Forty-seven out of 75 patients were male, and the mean age was 50 (± 17.9) years. Hemorrhoids were classified as Goligher’s degree II in 25 cases, III in 40 and IV, simple irreducible without ischemic changes, in 10. The mean operative time was 35 (28-60) minutes, and most procedures were performed with epidural anesthesia (80%). No intraoperative complications occurred, and 73 patients (97.3%) were discharged within post-operative day 1. Early post-operative pain and bleeding occurred in 37.3% and 8% of patients, respectively. No patients experienced anal incontinence and severe symptoms at 6 months after surgery. The overall success rate was 97.3%. Conclusions: THD is safe and effective in hemorrhoidal disease at degree II if bleeding, III, and IV at initial stage, both as a first intervention and on recurrence. Physician and patient need to understand each other’s expectations, weight the risks and benefits, and customize the treatment.